2017
DOI: 10.1037/xge0000302
|View full text |Cite
|
Sign up to set email alerts
|

Word and face processing engage overlapping distributed networks: Evidence from RSVP and EEG investigations.

Abstract: Words and faces have vastly different visual properties, but increasing evidence suggests that word and face processing engage overlapping distributed networks. For instance, fMRI studies have shown overlapping activity for face and word processing in the fusiform gyrus despite well-characterized lateralization of these objects to the left and right hemispheres, respectively. To investigate whether face and word perception influences perception of the other stimulus class and elucidate the mechanisms underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Almost certainly, distributed neural networks mediate both visual word and face processing (Harris et al, 2015; Robinson, Plaut & Behrmann, 2017). The degree to which nodes and connections in these networks overlap is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Almost certainly, distributed neural networks mediate both visual word and face processing (Harris et al, 2015; Robinson, Plaut & Behrmann, 2017). The degree to which nodes and connections in these networks overlap is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…This has important theoretical implications for how object recognition is organized in the visual system. The distributed view suggests that object processing is performed by networks of visual regions, and that some of these regions are involved in the perception of several types of stimuli 66– 68 . The modular view claims that different categories of objects—particularly faces—are processed by distinct dedicated cortical regions 69– 71 .…”
Section: Is Prosopagnosia Only About Faces?mentioning
confidence: 99%
“…Similarly, ECoG studies have reported both distinct and overlapping responses to faces and written words, with a bias for overlap towards the FG (Matsuo et al, 2013). The functional relevance of this overlap is contentious as it has been proposed to reflect shared neural circuitry (e.g., Behrmann and Plaut, 2013; Robinson et al, 2017) or distinct but spatially overlapping neural circuitry (e.g., Harris et al, 2016). While fMRI studies have examined the functional relationship between the neural patterns of faces and words in VOTC regions sensitive to words (Nestor et al, 2012) or defined anatomically (Harris et al, 2016), no studies have isolated and compared the selective responses (i.e., faces>control vs. words>control), and there is, to our knowledge, no iEEG data to complement the (few) fMRI studies on this topic.…”
Section: Discussionmentioning
confidence: 99%